1999
DOI: 10.1139/x99-007
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of human-induced vegetation changes in Sequoia National Park, California

Abstract: We resampled 76 permanent plots that had been established in the woodlands and forests of Sequoia National Park in 1969. Our objectives were to describe vegetation changes in the tree and shrub layers and determine the effects of prescribed burning that began in the 1960s. We compared changes in species importance and tree size class distributions between sample dates and between burned and unburned plots. Species composition had remained similar in all nine vegetation types sampled except in the ponderosa pin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
4
1
Order By: Relevance
“…Associations between estimated fire history and blue oak regeneration drawn from dendrochronological studies (McClaren and ) result because fire temporally concentrates shoot ages of sprouts through topkill. Although other studies that report on direct effects of fire on blue oak have involved either larger (Haggerty 1994, Roy andVankat 1999) or smaller (Allen-Diaz andBartolome 1992, Schwan andothers 1997) oaks than those in our study, none of these studies provide evidence that fire favors blue oak regeneration.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…Associations between estimated fire history and blue oak regeneration drawn from dendrochronological studies (McClaren and ) result because fire temporally concentrates shoot ages of sprouts through topkill. Although other studies that report on direct effects of fire on blue oak have involved either larger (Haggerty 1994, Roy andVankat 1999) or smaller (Allen-Diaz andBartolome 1992, Schwan andothers 1997) oaks than those in our study, none of these studies provide evidence that fire favors blue oak regeneration.…”
Section: Discussioncontrasting
confidence: 77%
“…In a previous study on blue oak sapling recruitment in 15 locations, we found that sapling recruitment was not dependent upon fire and that repeated fires reduced sapling populations (Swiecki and others 1997). Similarly, Roy and Vankat (1999) found no blue oak regeneration when they resurveyed plots in Sequoia National Park, some of which had burned. Mortality of mature trees was greater in burned plots, but the paper does not report whether the differences were statistically significant.…”
Section: Introductionmentioning
confidence: 99%
“…If understory trees were undergoing self‐thinning, we would expect both increasing stand biomass and gradually decreasing mortality rates (Peet & Christensen 1987) instead of unchanging stand biomass and increasing mortality rates. Additionally, many of our forest plots are in higher elevation forests that are currently close to their historic fire return intervals (Pitcher 1987), while lower elevation forests have had 100–140 years since the cessation of burning to attain quasi‐equilibrium (Swetnam 1993; Roy & Vankat 1999). Finally, mortality rates are increasing for both the shade‐tolerant Abies and generally shade‐intolerant Pinus , and canopy closure – as reflected in cumulative tree size (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The Southern Sierra Nevada mountains are also home to the largest trees in the world (Giant Sequoias Sequoiadendron giganteum); although these trees did not occur within the footprint of the available LiDAR imagery, the climate is very similar to the mid-elevation transition sites 31 (Soaproot Saddle/ Providence Creek) and these isolated pockets of Sequoias will also experience Southern Sierran climatic changes in the next century. Extensive human management and fire in these forests has affected species composition and structure, highlighting the importance of anthropogenic influences on the forests of the Southern Sierra Nevada (Roy and Vankat, 1999).…”
Section: Management Implicationsmentioning
confidence: 99%